2018
DOI: 10.1038/s41598-018-30686-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor efficacy of Selinexor (KPT-330) in gastric cancer is dependent on nuclear accumulation of p53 tumor suppressor

Abstract: Exportin-1 (XPO1) controls the nucleo-cytoplasmic trafficking of several key growth regulatory and tumor suppressor proteins. Nuclear export blockade through XPO1 inhibition is a target for therapeutic inhibition in many cancers. Studies have suggested XPO1 upregulation as an indicator of poor prognosis in gastric cancer. In the current study, we investigated the anti-tumor efficacy of selective inhibitors of nuclear export (SINE) compounds KPT-185, KTP-276 and clinical stage selinexor (KPT-330) in gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 38 publications
(42 reference statements)
2
68
0
Order By: Relevance
“…Our previous study concerned of p53, reported that the XPO1 positivity was associated with loss of p53 expression in CRC tumors with lymph node metastasis (Aladhraei et al, 2019). In the current study, we noticed a significant apparent of XPO1 overexpression in CRC tumor cells compared to the adjacent normal epithelium as it was reported in many other types of cancers such as esophageal (van der Watt et al, 2014), gastric (Subhash et al, 2018), lung (Gao et al, 2015), and ovarian (Noske et al, 2008) cancers, as well as leukemic cells (Kojima et al, 2013). The overexpression of XPO1 within the tumor cells may reflect its abundance and suggests a gain-of-function or oncogenic activity in line of further CRC pathogenesis (Conforti et al, 2015).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our previous study concerned of p53, reported that the XPO1 positivity was associated with loss of p53 expression in CRC tumors with lymph node metastasis (Aladhraei et al, 2019). In the current study, we noticed a significant apparent of XPO1 overexpression in CRC tumor cells compared to the adjacent normal epithelium as it was reported in many other types of cancers such as esophageal (van der Watt et al, 2014), gastric (Subhash et al, 2018), lung (Gao et al, 2015), and ovarian (Noske et al, 2008) cancers, as well as leukemic cells (Kojima et al, 2013). The overexpression of XPO1 within the tumor cells may reflect its abundance and suggests a gain-of-function or oncogenic activity in line of further CRC pathogenesis (Conforti et al, 2015).…”
Section: Discussionsupporting
confidence: 76%
“…The above results fall in-line with the published data about the KPT-330 ability to sequester the cargoes such as tumor suppressor proteins within the nucleus and leads to cell cycle arrest and proliferation inhibition. The anti-proliferative effect of XPO1 inhibitors were reported in different types of cancer cell lines such as pancreatic cells (Azmi et al, 2017), liver cells (Zheng et al, 2014), prostate cells (Gravina et al, 2015), and gastric cells (Subhash et al, 2018) as well as in colon cancer cell lines (Draetta et al, 2011;Niu et al, 2015). In conclusion, an apparent of XPO1 overexpression in CRC tumor cells compared to the adjacent normal epithelium as well as the association of XPO1 overexpression with advance tumor stages, tumor differentiation and high Ki67 expression may reflect its potential involvement in CRC pathogenesis which can be inhibited by KTP-330.…”
Section: Overexpressionmentioning
confidence: 99%
“…Although the anti-tumoral activity of XPO1 inhibitors is not fully understood, a recent study has shown that the XPO1 inhibitor selinexor conceivably exerts its function by reducing the p53 export out of the nucleus, thus enhancing p53 nuclear retention (Figure 4) [92]. This hypothesis has been also corroborated by the fact that selinexor upregulates the transcription of p53 target genes coding for anti-apoptotic proteins and for proteins that lead to cell cycle arrest such as p21 [94].…”
Section: Targeted Therapies That Potentiate P53 Functionmentioning
confidence: 91%
“…However, cancer cells may progressively acquire intracellular mechanisms for exclusion from the nucleus of tumor suppressor proteins [7]. Remarkably, a fraction of CLL carries mutations of XPO1, that are known to enhance p53 export from the nucleus to the cytoplasm [94]. Inhibiting XPO1, eg with Selinexor, may restore p53 localization to the nucleus and normal function.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation